The Role and Importance of Composition Science in The Development of Analytical Thinking of Future Visual Arts Teachers - Ruziyev Jonibek (Genius Publishing Group, 2024)
The article gives a detailed idea of the important aspects of compositional concepts in the visual art of portrait genre artists.
Keywords: Portrait; composition; graphics; perspective